Applying good budgeting practices to health - Vammalle, Camila (OECD Publishing, 2023)
This journal article presents a set of high-level good budgeting practices in the health sector. The purpose of these good practices is to support countries in assessing their own budgeting arrangements for health, and in designing budgeting reforms. The article builds on 10 years of work by the OECD Joint Network of Senior Budget and Health Officials
Keywords: Finance and Investment; Governance; Economics